Pengaruh Kualitas Pelayanan dan Lingkungan Kerja Fisik terhadap Kepuasan Pelanggan PDAM Muara Teweh Kabupaten Barito Utara - Sumiati Sumiati; M. Noor Rasyidi; Hereyanto Hereyanto (JURNAL BISNIS DAN PEMBANGUNAN, 2018)
This study aimed to examine the effect of Quality Service (X1) and the Physical Environment (X2) of the Customer Satisfaction (Y) on taps Muara Teweh North Barito regency Samples taken as many as 65 customers selected by accidental sampling technique. Collecting data using questionnaires, while data analysis using SPSS. The test results prove the Quality Service (X1) a significant effect on customer satisfaction (Y) partially with great influence 60.7% and the Physical Environment (X2) not significant effect on customer satisfaction (Y) partially with great effect 8.7 %, while simultaneously Quality Service (X1) and the Physical Environment (X2) significantly affects customer satisfaction (Y) with the influence of 34.9% while the remaining 65.1% is influenced by other variables.  Keywords: Quality Service, Physical Environment, Customer Satisfaction.